Innovation and international business: A systematic literature review - Aldeanueva-Fernández, Ignacio (Elsevier, 2023)
Introduction: Innovation and international business are essential to achieve competitive advantages in currently unforeseen business environments. Today’s company seeks innovation in its country of origin and abroad in order to compete globally. Thus, incorporating this concept into international companies’ strategies is a main issue nowadays. Purpose: The aim of this systematic study is to improve the current knowledge on the relationship between innovation and international business, as well as identifying innovation tendencies for corporations to acknowledge the opportunities and challenges of this area’s development in the international business context. Methodology: Despite the abundance of innovation and international business reviews, joint reviews of both of them cannot be found. This study is the first to combine the scholarly research on both topics with the systematic literature review of academic literature of 28 years, following the PRISMA guidelines and flowchart. A search was carried out in Web of Science database; 847 initial documents were obtained and, after reviewing multiple documents according to the inclusion/exclusion criteria, the results for this research work were reduced to 236 articles.
Keywords: Multinacionales; Innovation; International business; Systematic review; Multinational corporation; Knowledge